Early preeclampsia is associated with persistence of hypertension 3 months postpartum in women: an observational study at a tertiary hospital in Brazil - Gustavo Moleiro Tallarico; Priscila Oliveira Barbosa; Luiz Sérgio Lima-Junior; Ricardo Carvalho Cavalli (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study aimed to investigate the persistence of hypertension at three months postpartum in women who experienced preeclampsia during pregnancy. Methods: A prospective observational study at Hospital das Clínicas de Ribeirão Preto, Brazil, included 24 women. Blood pressure measurements and/or antihypertensive use were assessed, alongside risk factors such as body mass index (BMI), heart rate, lipid profile and C-reactive protein (CRP). Data on demographic, obstetric and lifestyle factors were also collected. Results: Out of 24 postpartum women enrolled in this study, 15 (62.5%) of participants remained hypertensive three months after delivery. Women with early-onset preeclampsia had a 2.36-fold increased risk of persistent hypertension at three months postpartum. No significant differences were found among risk factors for persistent hypertension. Conclusion: Our results indicate a high prevalence of persistent hypertension in women with preeclampsia in Brazil. The findings highlight the need for extended monitoring specially in early onset preeclampsia and targeted lifestyle interventions.